COVID-19 vaccine uptake in Zimbabwe and Sierra Leone: an application of Health Belief Model constructs - Simon Ssentongo; Alex Muhereza; Morie Mustapha; Ruth Gemi; Dennis Cherian; Rebecca Waugh; Benjamin Crookston; Cougar Hall; Mary Linehan; Hayden Borg; Joshua West (BMC Public Health)
Abstract Introduction While African countries, in general, experienced a milder COVID-19 impact compared to Western nations, they faced challenges with vaccine uptake. Specifically, Zimbabwe and Sierra Leone saw vaccine acceptance rates below global averages. This research delves into the underlying factors that influenced these disparities in vaccine acceptance in these two countries, using the Health Belief Model (HBM) and the Theory of Planned Behavior (TPB) as guiding frameworks. Methods This study utilized data from a cross-sectional survey encompassing 2,312 participants from areas where the Africa Christian Health Associations Platform (ACHAP) operates in Zimbabwe and Sierra Leone. The survey assessed respondents' views in line with core HBM and TPB constructs, in addition to their levels of vaccine acceptance. We then employed adjusted logistic regression models to investigate the correlation between health behavior change theory constructs and vaccine uptake, taking into account variables like gender, age, education, and country of residence. Results Several associations were identified, including high vaccine uptake correlated with a heightened perceived threat of COVID-19 (OR = 2.674; p < .001), recognized benefits of vaccination (OR = 1.482; p < .001), stronger perceived behavior control (OR = 2.189; p < .001), and fewer perceived barriers to vaccination (OR = 0.173; p < .001). Conversely, low vaccine uptake was linked to diminished perceived threats (OR = 0.540; p < .001), fewer perceived benefits (OR = 0.762; p < .001), weaker perceived behavior control (OR = 0.429; p < .001), and heightened perceptions of barriers (OR = 2.001; p < .001). Conclusion Results underscore the significance and utility of theoretical constructs in understanding variations in vaccine uptake levels. They highlight the importance of relying on well-established theories to grasp decision-making mechanisms and to shape suggestions for behavior modification. Consequently, to boost vaccine acceptance, public health campaigns should focus on reshaping risk perceptions, addressing obstacles, emphasizing the advantages of getting vaccinated, and fostering a sense of self-efficacy within target communities.